2012
DOI: 10.3109/09513590.2011.650766
|View full text |Cite
|
Sign up to set email alerts
|

Serum lipid levels and bone mineral density in Greek postmenopausal women

Abstract: Contradictory results have been reported regarding a relationship between serum lipid levels and bone mineral density. The purpose of this study was to further investigate a possible relationship between those parameters in Greek postmenopausal women. A total of 591 patients followed at a tertiary hospital were examined for seven different lipid factors in relation to dual-emission X-ray absorptiometry measurements at the lumbar spine. Lipoprotein-a was the only lipid measurement that univariately showed an al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
1
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 33 publications
2
14
1
3
Order By: Relevance
“…Many studies do not support strong association between lipids' concentrations and bone mass measurements [38]. In this study, we report also a weak relationship between lipid levels and BMD in SCI population.…”
Section: Discussioncontrasting
confidence: 70%
“…Many studies do not support strong association between lipids' concentrations and bone mass measurements [38]. In this study, we report also a weak relationship between lipid levels and BMD in SCI population.…”
Section: Discussioncontrasting
confidence: 70%
“…[14] Few studies have also shown no relationship between TC and LDL-c with BMD at any site. [5781619] Several of these studies are weakened by either small sample size,[511] selection bias,[19] or inclusion of subjects with comorbidities, as well as and consumption of medication known to affect BMD. [5]…”
Section: Discussionmentioning
confidence: 99%
“…Studies evaluating the relationship between lipid parameters and bone mineral density (BMD) in healthy adults and those with metabolic syndrome have revealed inconsistent results. [34567891011121314151617181920212223242526] While most of the studies have been performed in women, there are a few studies in men[345678] and adolescents. [5] Since Indians have differences in lipid profiles [higher prevalence of high triglycerides (TGs) and low high density lipoprotein cholesterol] compared with other populations,[27] we assessed the relationship between various lipid parameters with BMD at different sites in previously conducted cross-sectional population in healthy Indian volunteers.…”
Section: Introductionmentioning
confidence: 99%
“…The results are debatable because both positive and negative relationships have been found. Besides, few studies indicated no significant association between lipid levels and BMD …”
Section: Introductionmentioning
confidence: 99%
“…Besides, few studies indicated no significant association between lipid levels and BMD. 9,10 The potential explanations for these associations may be the coexistence factors of osteoporosis and age-independent atherosclerotic calcification including oxidized lipids, leptin and osteoprotegerin. 11 Several receptors reside on both osteocytes and endovascular lining cells may play important roles in both systems.…”
Section: Introductionmentioning
confidence: 99%